Attractiveness and Sexual Competitiveness of Anastrepha obliqua Males (Diptera: Tephritidae) Fed on a Diet Enriched With Providencia rettgeri - Roque-Romero, Linnet; Hernández, Emilio; Aceituno-Medina, Marysol; Ventura, Carmen; Toledo, Jorge; Malo, Edi A. (Frontiers in Microbiology, 2020)
The West Indian fruit fly, Anastrepha obliqua (Macquart), is the second most important tephritid fruit fly in Mexico, infesting mango, hog plum and guava fruits. To control this pest, the Mexican government has implemented the use of the sterile insect technique (SIT), which involves the mass production, sterilization and release of flies. However, the A. obliqua laboratory males used in SIT are selected to a lesser extent by the wild females during competitiveness tests. The objective of this study was to compare the effects of males fed on fruit fly food enriched with Providencia rettgeri to those in males fed on food alone, assessing male mating competitiveness, capture of females using traps baited with males fed with the enriched diet and sex pheromone components. The results indicated that males fed with the diet enriched with P. rettgeri had increased mating competitiveness and captured more females in the field cage tests. However, no difference was observed in the proportion of volatile sex pheromone components identified during the calling of A. obliqua males. The results suggest the value of incorporating bacteria into the mass rearing technique of A. obliqua adults in order to improve the sexual competitiveness of males from the laboratory compared to wild males.